Game Design Education "Terjumlah" Using Kinect Sensor - Yedija Prima Putra; Erdhi Widyarto Nugroho; Hendra Prasetya (Journal of Business and Technology, 2021)
At present, the development of the game world is increasing. A lot of which utilize various sensors as input. However, many of these games have no educational value. Therefore, the game titled "Terjumlah" is designed, which has educational value, in this case math material. In the making of the game, collaborated using kinect sensor that can detect the movement of the user, to be more active and interactive.